Minimal primer and primer-free SELEX protocols for selection of aptamers from random DNA libraries. (March 2008) - Pan, Weihua; Xin, Ping; Clawson, Gary A.
Standard systematic evolution of ligands by exponential enrichment (SELEX) protocols require libraries that contain two primers, one on each side of a central random domain, which allow amplification of target-bound sequences via PCR or RT-PCR. However, these primer sequences cause nonspecific binding by their nature (generally adding about 20 nt on each end of the random sequence of about 30–40 nt), and can result in large numbers of false-positive binding sequences and/or interfere with good binding random sequences. Here, we have developed two DNA-based methods that reduce and/or eliminate the primer sequences from the target-binding step, thus reducing or eliminating the interference caused by the primer sequences. In these methods, the starting selection libraries contain a central random sequence that is: ( i ) flanked by only 2 nt on each side (minimal primer); or ( ii ) flanked only by either a 2- or 0-nt overhand on the 3′ end (primer-free). These methods allow primer regeneration and re-elimination after and before selection, are fast and simple, and don't require any chemical modifications for selection in a variety of conditions. Further, the selection rounds are performed with DNA oligomers, which are generally employed as end product aptamers.